Wireless Multiple Access and Analog Oscillation Analysis in Microgrids: A Prony Approach. (9th October 2012) - Gong, Shuping; Li, Husheng
Abstract : A key challenge in smart grid is to monitor the system modal characteristics of disturbance over a microgrid for system stability and diagnosis. The measurements at different phasor measurement units (PMUs) need to be reported to a processing center. Therefore, a multiple access scheme for wireless transmission is necessary to collect the measurements from PMUs. An analog oscillation analysis is carried out without demodulating the received signal. Both schemes of time-division multiple access (TDMA) and code-division multiple access (CDMA) are discussed. In both schemes, the Prony-based algorithms using the received signal to estimate the system modal characteristics, including the eigenvalues of the linear system and the amplitudes of different response modes, are proposed and analyzed. Two countermeasures, max-min ratio measure (MMRM) and variance measure (VM), are also proposed to prevent possible attacks of false reports. Numerical simulation results demonstrate the effectiveness of Prony-based algorithms and the two countermeasures.